WEED CONTROL AND SOYBEAN AGRONOMIC PERFORMANCE IN RESPONSE TO THE APPLICATION OF SULFENTRAZONE + DIURON IN PRE-EMERGENCE (Colloquium Agrariae. ISSN: 1809-8215, 2021)
The use of pre-emergent herbicides is an important tool in the management of weeds. The sulfentrazone + diuron mixture was recently launched onto the market. The aim of this work was to evaluate the weed control and the agronomic performance of soybean in response to the application of pre-emergence doses of sulfentrazone + diuron. The experiment was conducted in Londrina PR, in an oxisol. The treatments were doses of sulfentrazone + diuron (62 + 123, 123 + 245, 184 + 368, 245 + 490, 306 + 613 e 368 + 735 g a.i. ha-1). In addition to these treatments, isolated applications of sulfentrazone (245 g a.i. ha-1) and diuron (490 g a.i. ha-1) were evaluated, as well as an infested and weeded control. For the weed control, the wild radish and itchgrass emergence were evaluated. In soybean, PSII activity, stand, plant height, number of pods per plant, height of insertion of the first pod, number of nodes per plant, mass of a thousand grains and grain yield were evaluated. The mixture of sulfentrazone + diuron resulted in less than 50% wild radish control, regardless of the dose evaluated. However, for itchgrass, the control was satisfactory, being greater than 90% in doses from 123 + 245 g a.i. ha-1. Regarding the soybean crop, in doses from 245 + 490 g a.i. ha-1 there was a greater number of pods per plant and higher grain yield, not differing from the weeded control, with a yield of approximately 3,000 kg ha-1. The application of herbicides led to a transient inhibition of PSII activity, which did not result in a reduction in crop grain yield, indicating plant recovery. Therefore, the mixture of sulfentrazone + diuron is a good alternative for the management of weeds in pre-emergence of soybean culture, and should be positioned according to the history of field infestation.